Complete guide to preventive and predictive maintenance - Levitt, Joel (Industrial Press Inc., 2011)
Shares the best practices, mistakes, victories, and essential steps for success which the author has gleaned from working with countless organizations. This resource includes check sheets, history of PM, stories, photographs, and case histories. It also provides sample task lists for a variety of equipment with some of the logic behind each task